The Effectiveness of Learning Videos Measuring Length With Size Comparison Of Mathematics At Elementary High School Indramayu West Java - Elfa Yanti; Muhamad Sofian Hadi (English Language in Focus (ELIF), 2023)
ABSTRACT This study aims to test the effectiveness of using learning videos media, namely learning using videos about measuring length by comparing the length of an object, comparing length measurements for mathematics lesson class 1 SD N I Pekandangan Jaya Kab. Indramayu.In this research, the researcher used a per-experiment. To determine the effectiveness of using learning videos media, comparing length measurements for mathematics in class one elementary high school , in this research, theresearcher uses a per-experimental with a one-group pretest and post-testdesign. The instrument used in this study is the pretest and post-test. This pretest and post-test aim to determine the effectiveness of using learning videos media, comparing length measurement for mathematics  by students. The data analysis was done by comparing the calculation of to with t table to determine the hypothesis.This study used the pre-experimental  class method. By using the RnD method. So the learning outcomes using learning video media measuring length of these object can improve student learning outcomes from these result , learning videos comparing length sizes are very effective in student learning in the field of mathematics, especially grade 1 SD N Pekandangan Jaya . Kab. Indramayu.Keywoerds : Development , Mathematics , Learning Video , RnD.